2008
DOI: 10.1136/gut.2008.161927
|View full text |Cite
|
Sign up to set email alerts
|

Paradox of gastric cardia: it becomes more acidic following meals while the rest of stomach becomes less acidic

Abstract: Whereas the rest of the stomach shows a marked fall in acidity on ingesting a meal, the cardia paradoxically increases in acidity to become the most acidic region throughout the postprandial period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 25 publications
4
30
0
12
Order By: Relevance
“…Grigolon et al ( 22 ) timed the fi rst onset of the acid pocket using a BRAVO pH capsule 2 cm below the lower esophageal sphincter (LES) and found the median time for onset of the acid pocket was 14 min. A number of other studies corroborate this and have demonstrated that the pocket persists for up to 90 min aft er meals ( 14,17,19 ). In one study, real-time recording of fasting and postprandial luminal pH with a 12 pH electrode assembly allowed close observation of the dynamic changes to esophageal and stomach pH over time ( 14 ).…”
Section: Reviewsupporting
confidence: 55%
See 3 more Smart Citations
“…Grigolon et al ( 22 ) timed the fi rst onset of the acid pocket using a BRAVO pH capsule 2 cm below the lower esophageal sphincter (LES) and found the median time for onset of the acid pocket was 14 min. A number of other studies corroborate this and have demonstrated that the pocket persists for up to 90 min aft er meals ( 14,17,19 ). In one study, real-time recording of fasting and postprandial luminal pH with a 12 pH electrode assembly allowed close observation of the dynamic changes to esophageal and stomach pH over time ( 14 ).…”
Section: Reviewsupporting
confidence: 55%
“…A number of other studies corroborate this and have demonstrated that the pocket persists for up to 90 min aft er meals ( 14,17,19 ). In one study, real-time recording of fasting and postprandial luminal pH with a 12 pH electrode assembly allowed close observation of the dynamic changes to esophageal and stomach pH over time ( 14 ). Recordings clearly demonstrated that the gastric cardia paradoxically became more acidic aft er a meal while the rest of the stomach became less acidic.…”
Section: Reviewsupporting
confidence: 53%
See 2 more Smart Citations
“…They confirmed the maximal acidity at the cardia occurred around 60 to 70 minutes after the meal. 13 …”
Section: High-resolution Ph Studiesmentioning
confidence: 97%